Boogie - Muntean, Radu; Lucaciu, Tudor; Bucur, Dragos; Marinca, Anamaria; Branescu, Mimi (Dogwoof, 2009)
Boogie (2008): Having captured the chaos that followed the collapse of the Ceausescu regime in "The Paper Will Be Blue" in 2006, Romanian director Radu Muntean moves on to more universal themes in this sombre seaside drama. Married couple Bogdan (Dragos Bucur) and Smaranda (Anamaria Marinca) refuse to let a chill wind spoil their May Day break with their toddler son. But it also blows Bogdan's footloose school buddies (Mimi Branescu, Adrian Vancica) back into his life after several years and it only takes a few drinks for the thirtysomething father to wonder whether he's made the right decision in settling down. Making adroit use of enclosed spaces and mundane dialogue, Muntean conveys the mix of nostalgia, disappointment and doubt that lures Bucur away from his pregnant wife and into the company of a hooker (Roxana Iancu). But it's the political implications of the action that are so disconcerting, as the film questions the advisability of both onerous stability and hazardous change. [www.radiotimes.com]